2000
DOI: 10.1097/00003246-200006000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Ornithine α-ketoglutarate improves wound healing in severe burn patients: A prospective randomized double-blind trial versus isonitrogenous controls

Abstract: Ornithine alpha-ketoglutarate supplementation of enteral feeding significantly shortens wound healing time in severe burn patients. In addition, ornithine alpha-ketoglutarate administration was safe and well tolerated and decreased protein hypercatabolism in the less severe burn patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(30 citation statements)
references
References 26 publications
1
25
0
4
Order By: Relevance
“…In addition, a-KG dramatically increases the synthesis of arginine, proline, and polyamines, which also play key roles in metabolic adaptation after surgery. Furthermore, the recent literature suggests that a-KG improves gut morphology and functions, counteracts traumainduced dysimmunity, and exerts anabolic/anti-catabolic actions on protein metabolism [9][10][11]. 5-HMF is a common product of the Maillard reaction, which occurs in many foods and drinks (dried fruits, honey, caramel products) in high concentrations exceeding 1 g/kg [12].…”
Section: Surgical Resection Remains the Treatment Of Choice For Non-smentioning
confidence: 99%
“…In addition, a-KG dramatically increases the synthesis of arginine, proline, and polyamines, which also play key roles in metabolic adaptation after surgery. Furthermore, the recent literature suggests that a-KG improves gut morphology and functions, counteracts traumainduced dysimmunity, and exerts anabolic/anti-catabolic actions on protein metabolism [9][10][11]. 5-HMF is a common product of the Maillard reaction, which occurs in many foods and drinks (dried fruits, honey, caramel products) in high concentrations exceeding 1 g/kg [12].…”
Section: Surgical Resection Remains the Treatment Of Choice For Non-smentioning
confidence: 99%
“…This data corroborates the RCT with 47 participants which examined the effectiveness of OKG compared with isonitrogenous control in the healing of severely burned patients. It was found that the healing time of wounds in patients receiving OKG was lower compared to the control (60 ± 7 vs 90 ± 12 days; p <0.05) (30) .…”
Section: Discussionmentioning
confidence: 86%
“…These three-pronged benefits inherent in ketoacids that involve the reduction of ROS, production of Lcarnitine and charging of the mitochondria with appropriate fuels will increase ATP production, a factor at the root cause of AD (40). Ketoacids have been utilized in remedying renal dysfunction, muscle fatigue, heart defects and burns (58,59,60). In a more recent example, L-arginine's positive effects on supplementation of energy expenditure regardless of age, previous incidence of diseases or activity shows promise as a metabolite therapy (61).…”
Section: A Metabolite-based Therapy For Admentioning
confidence: 99%